From Parody to Rewriting: Margaret Mitchell’s GoneWith the Wind (1936) vs Alice Randall’s The Wind Done Gone (2001) - Isabelle Roblin (Revue LISA)
When after many difficulties, Alice Randall published The Wind Done Gone, the question of the very nature of the novel came to the foreground, from a constitutional as well as a literary standpoint: was it a parodic re-writing of Margaret Mitchell’s Gone With the Wind, and as such protected by the First Amendment; or was it just a “steal” of famous characters and situations, and as such submitted to the strict laws of copyright? The analysis of the various literary devices used by the author will show the subversive nature of the hypertext, which goes beyond simple parody.